PENGEMBANGAN MODEL PEMBELAJARAN TALKING STICK DENGAN MEMANFAATKAN BARANG BEKAS UNTUK MENINGKATKAN FISIK MOTORIK DAN BAHASA ANAK DI PAUD KB CERIA (STUDY PAUD KB CERIA PASAR SUKADANA LAMPUNG TIMUR) - Siti Sundari (UNISAN JURNAL, 2024)
The purpose of this study was to be able to improve Active and Creative Students and Teachers at Darun Nadwah IT Kindergarten and to form painstaking participants and fun learning models in the teaching and learning process in the play area while learning children. This research is a development research that uses a model of classroom action research conducted in two cycles, each of which consists of stages of planning, implementation, observation, and reflection. The results of this study are the physical and language levels of the activities using the Talking Stick learning model by utilizing second-hand items in the PAUD KB Ceria Sukadana. In this activity involving all kindergarten children in PAUD KB Ceria Sukadana is still undeveloped. The results of the study of increasing motoric and children’s language using the Talking Stick learning model in the first cycle of values obtained an average of 5.54 with 75% classical learning completeness with criteria starting to develop. In the second cycle more increased with an average value of 9.58 with 65% classical learning completeness with criteria developed according to expectations. This shows that the Talking Stick learning model by utilizing second hand items can improve the physical motives and language of kindergarten children in PAUD KB Ceria Sukadana Keywords: motoric, children’s language skills, the Talking Stick learning mode, utilizing used items